Komunikasi Eksternal Divisi Hubungan Masyarakat Kepolisian Republik Indonesia - Mukaromah, Amalia; Sitorus, Onny Fitriana (Utilitas, 2016)
This research aims to find out how external communication in public relations Division of the national police. This research takes data from three informants, namely the head of sub-Division of the news section of the public lighting bureau public relations Division community police, head of the ministry of information and documentation bureau manager documentation information public relations Division of the police, administrative officer and part of the ministry of information and documentation. In the study, researchers conducted the sample and the data source selected by purposive and snowball sampling. This research uses qualitative research methods, descriptive. Data collection methods used were observation, interviews, and documentation. Based on the results of the research was undertaken researchers then it can be inferred that the external communications on the public relations Division of the national police are divided into two linesconsist of (1) communication from the organization to a wider audience that is informative tailored to Act No. 14 of the year 2008 about the openness of public information delivered through several activities and by using the media.The openness of institutions do to get the public trust to the institutions; (2) Communication from the audience to the organization that is the public relations Division police get feedback and opinions from the community in the form of a negative and a positive response by observing the mass media, online media, public relations activities conducted and the police sources trustworthy of the policies conducted by the ranks of the police force of the Republic of Indonesia andthe information submitted public relations Division of the national police.